The Meaning of “Natural” - Rozin, Paul (Psychological Science, 2005)
The meaning of the desirable attribute “natural” was explored in two samples, American college students and adults in the Philadelphia jury pool. Participants rated the naturalness of a variety of “natural” entities, before and after they were transformed by operations such as freezing, adding or removing components, mixing with other natural or unnatural entities, domestication, and genetic engineering. Results support four hypotheses. First, the principle of contagion accounts for many aspects of the reduction of naturalness by contact with unnatural entities. Second, chemical transformations reduce naturalness much more than physical transformations do. Third, the history of an entity's processing is more important in determining its naturalness than is the nature of the entity's contents. Fourth, mixing like natural entities (e.g., water from different sources) does not markedly reduce naturalness. The insertion of a gene from another species, the process used in producing genetically modified organisms, produces the biggest drop in naturalness; domestication, a human-accomplished activity that changes genotype and phenotype in major ways, is considered much less damaging to naturalness.